Quality improvement capacity: a survey of hospital quality managers. Issue 1 (19th February 2010) - Gagliardi, A R; Majewski, C; Victor, J C; Baker, G R
Abstract : Background: Skilled managers are an important component of quality improvement (QI) infrastructure, but there has been little evaluation of QI infrastructure, which is needed to guide enhancement of this capacity. Methods: Quality managers at 97 acute care hospitals in Ontario, Canada, were surveyed by mail to describe how their roles were integrated with QI performance objectives. Binary and scaled responses were analysed quantitatively, and open-ended responses were analysed thematically. Results: The response rate was 79.4%. Many QI managers were new to their role and had no support staff despite responsibility for multiple portfolios. Respondents thought that QI objectives should be less reactive to hospital executives or boards, adverse events or demands from government and accreditation bodies, and recommended that dedicated QI managers proactively apply explicit strategic plans and engage executives and clinicians. Findings were consistent regardless of rank, staffing or hospital type. Those with master's training and greater experience were more involved in strategic planning, data analysis and communication. Conclusions: QI is not well resourced in most acute care hospitals in Ontario. To develop QI capacity, investment and QI training may be required. Research should empirically establish objective performance measures of QI capacity to guide investment and evaluation.